Whistleblowing sebagai Manifestasi Etika dalam Bisnis Islam - Fauziyah, Nurul; Hasyim, Fuad (Jurnal Ilmiah Ekonomi Islam, 2024)
The widespread corruption cases in Indonesia have resulted in the country's Corruption Perception Index (CPI) score falling below the global average. This prevalence of corruption is certainly in stark contrast to the principles of business ethics in Islam. One concrete effort to uncover corruption is believed to be through whistleblowing. This study examines the role of whistleblowing as a manifestation of business ethics in Islam. Through a library research approach, this study analyzes the concept of whistleblowing within the context of Islamic business ethics, the ethical values underlying the practice of whistleblowing, as well as the obstacles and challenges that may be encountered in its implementation. The findings of the study indicate that Islamic ethical values, such as honesty, justice, and social responsibility, are represented through whistleblowing in Islamic business ethics. In the Qur'an, Allah SWT commands His servants to always do good and avoid wrongdoing, which aligns with the implementation of whistleblowing aimed at exposing fraud that harms the public